2006
DOI: 10.2353/ajpath.2006.051107
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Amyloid Angiopathy and Aβ Plaque Burden after Enriched Housing in TgCRND8 Mice

Abstract: Alzheimer's disease (AD) is the most prevalent form of senile dementia worldwide. It is characterized by two major histological hallmarks: senile plaques, ie, extracellular deposits mainly consisting of ␤-amyloid (A␤), and neurofibrillary tangles, ie, intracellular accumulations of hyperphosphorylated tau protein.1 AD patients show progressing cognitive decline as well as noncognitive behavioral symptoms such as wandering, sleep disturbance, and physical aggression.2 There are various risk factors for AD inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 51 publications
2
55
0
1
Order By: Relevance
“…3), has also been described as part of AD pathogenesis (22,68). One of the genes grouped in this pathway is cullin 3, which encodes an essential component of the ubiquitin E3 ligase complex.…”
Section: Discussionmentioning
confidence: 99%
“…3), has also been described as part of AD pathogenesis (22,68). One of the genes grouped in this pathway is cullin 3, which encodes an essential component of the ubiquitin E3 ligase complex.…”
Section: Discussionmentioning
confidence: 99%
“…189 A reduction in brain b-amyloid deposition after EE exposure has also been shown in APP, TgCRND8 and AD11 transgenic mice. 186,187,190,191 Some studies have also investigated the effects of EE on neurogenesis in AD mouse models. Although conditional PS1 knockout mice and mice overexpressing either wild-type human PS1 or the mutant form P117L show a deficiency in EE-induced neurogenesis, [192][193][194] it has been recently reported that EE promotes hippocampal neurogenesis in APP and TgCRND8 mice.…”
Section: Impact Of Ee On the Brain L Baroncelli Et Almentioning
confidence: 99%
“…Regular aerobic exercise has been shown to enhance performance on cognitive tasks in aged humans [1][2][3][4][5][6] and in learning and memory tests in animals. [7][8][9][10][11][12][13] In addition, physical exercise may be protective against Alzheimer's disease 8,9,[14][15][16][17][18][19][20] and may enhance recovery from both stroke [21][22][23][24][25] and traumatic brain injury. 11 However, the changes in brain morphology and function underlying these effects remain incompletely understood.…”
Section: Introductionmentioning
confidence: 99%